Determination of the energy standards by precision beta-spectroscopy methods - Kupryashkin, V.T.; Lashko, A.P.; Lashko, T.N.; Feoktistov, A.I.; Khomenkov, V.P. (Вопросы атомной науки и техники, 2004)
The technique allowing one to determine energy of transitions in atomic nuclei with high accuracy is developed. It is based on measurement of a difference of energy of internal conversion electron lines on high-resolution β- spectrometer π SQRT(2) with iron yoke and radius of an equilibrium orbit r = 50 cm at a constant magnetic spectrometer field. The accuracy of definition of γ-ray energies reaches from 0,2 up to 1 eV in the energy region from 100 up to 500 keV. That completely corresponds to the requirements to energy standards of 4-th order.